Daniel Harding and Charles Dutoit conduct 20th-century masterpieces - With Yuja Wang, Christoph Prégardien, David Guerrier, and Renaud Capuçon Verbier Festival 2010 - Prokofiev, Sergey 1891-1953; Britten, Benjamin 1913-1976; Stravinsky, Igor 1882-1971 (Idéale Audience, medici.tv, Arte France, 2010)
A concert of 20th-century masterpieces featuring an exceptional group of musicians ... Accompanied by the Verbier Festival Chamber Orchestra under the baton of Charles Dutoit, Yuja Wang takes on Prokofiev's Piano Concerto No. 2 in G Minor, the composer's second of five piano concertos that was lost and then rewritten in 1923. Then, Christoph Prégardien, David Guerrier, and Renaud Capuçon take the stage with the Verbier Festival Chamber Orchestra to perform Britten's Serenade for Tenor, Horn, and Strings, composed after a cycle of English poems. Daniel Harding and the Verbier Festival Orchestra close the concert with Stravinsky's celebrated Rite of Spring, whose premiere created an artistic scandal in 1913
Keywords: Songs (High voice) with chamber orchestra; Concertos (Piano); Ballets; Songs; Concertos; Concert films; Ballets (Music); Internet videos